Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Motivasi Kerja Karyawan Pada PT. Pilot Pen Indonesia - Vabiandra Adrell Ravarelly; Novita Wahyu Setyawati; Indah Rizki Maulia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The objective of this research is to determine the influence of the Work Environment and Organizational Culture on Employee Work Motivation at PT Pilot Pen Indonesia. This research produces variables that influence each other with this brief explanation, namely: 1). In the Work Environment variable, it obtained a significant value of 0.008 < 0.05 with a calculated t value of 2,691 > t table 1.657, so it means that the Work Environment has a positive and significant effect on Work Motivation. 2). In the Organizational Culture variable, a significant value of 0.000 < 0.05 was obtained with a calculated t value of 11,134 > t table 1.657, so it means that Organizational Culture has a positive and significant effect on Work Motivation. 3). The Work Environment and Organizational Culture variables obtained a significant value of 0.000 < 0.05 with a calculated f value of 182,560 > f table 3.070 so that H1 and H2 were accepted, and a coefficient of determination value of 0.757 or 75.7% was obtained, meaning that the Environment Work and Organizational Culture simultaneously have a positive and significant effect on Work Motivation. With the remaining 24.3% being influenced by other variables not included in this study.